Nationwide surveillance algorithms for tuberculosis among immigrant workers from highly endemic countries following pre-entry screening in Taiwan - Mei-Mei Kuan (BMC, 2018)
Abstract Background This cross-sectional study was retrospectively performed to assess the trend of tuberculosis (TB) among Taiwan's immigrant workers from highly TB-endemic countries under an intervention of conducting a 4-round follow-up (at 0-3 days and 6, 18, and 30 months post-migration) screening program with initial chest X-ray (CXR) following an overseas, pre-entry normal CXR. Methods The immigrant workers with TB disease enrolled in the Taiwan TB registry database in 2011-2014 were analyzed and linked to an immigrant worker physical exam database to stratify TB case categories of actively screened or not for comparison. Results Following pre-entry screening for the admission of CXR-normal immigrant workers from highly endemic countries, the overall TB incidence of 70.6-128.6/100,000 person-years resulted either from a subsequent series of 4-round post-entry active screenings or misalliance algorithms, including passive diagnostics for the illness. Overall, the TB relative risk based on incidence in the immigrant working population was 2.2- to 5.5-fold greater than that among corresponding age Taiwanese, with 14.3% (15.5/100,000 person-years) sputum-smear-positive pulmonary TB (SS+ PTB), 74.2% (80.8/100,000 person-years) sputum-smear-negative (SS-) PTB, and 7.8% (8.5/100,000 person-years) only extra-pulmonary TB (EPTB). Regarding the clinical characteristics, 55.5% TB cases - identified through passive illness diagnostics vs. 44.5% TB cases actively identified through mandatory screenings, were higher in SS+ PTB (adjusted odds Ratio (aOR): 1.5, 95% CI: 1.1-2.0, P = 0.008), higher in SC+ PTB (aOR: 1.4, 95% CI: 1.1-1.7, P = 0.004), higher in concurrent extra-pulmonary TB (aOR: 8.9, CI: 4.5-7.4, P < 0.001), and higher in normal CXR TB (aOR: > 100, CI: 0- > 100, P = 0.908). The TB yields of 3rd- to 4th-round screenings were higher than those of 1st- and 2nd-round screenings and ranged from 52.6-65.3 cases per 100,000 screenings in 2013-2014. Conclusions The multiple post-entry TB screenings with initial CXR for high-risk immigrants could actively reduce TB transmission by finding SS- TB cases at early stages. The TB yields at post-entry 3rd- to 4th-round screenings might imply a persistent reactivation of latent TB. Adding more sensitive, economical screenings and preventive treatments for latent TB infection is a comprehensive approach for accelerating TB elimination.